Penerapan Protokol Kesehatan Tanggap Covid-19 di Lingkungan Pondok Pesantren Al-Falah - Muh. Arif; Abdul Aziz Adam; Farhan Bonde; Frizkiyawati Yasin (Pusat Riset dan Inovasi Nasional, 2022)
This study aims to describe the implementation of Covid-19 response health protocols in the Al-Falah Islamic boarding school environment. The research conducted was descriptive with a qualitative approach. The data collection technique used was interviews and observations conducted for one month. Data is analyzed through the process of data collection, data reduction, data presentation, and conclusions. The results showed that the implementation of health protocols in Islamic boarding schools was running, but there were some things that were not optimal. The service carried out by students includes the implementation of stricter health protocols by procuring supporting facilities, participating in mentoring and coaching in routine student learning activities, and playing an active role in maintaining facilities and cleanliness of Islamic boarding schools.